Notes for "Welcoming Remarks" to Participants of Banquet Program Held by Channel Islands Chapter Non-Commissioned Officers Association - Jane Tolmach:::::: (1973)
Notes for a speech welcoming members to the dinner and discussing the relationship between Oxnard and the military.